(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Recurrent miscarriage is a medical condition characterized by two or more spontaneous abortions, which can be precipitated by various factors. The etiology of RM is complex and involves a wide range of intricate factors, primarily including genetic predisposition, immunological abnormalities, structural abnormalities, endocrinological dysregulation, and infectious agents. However, despite extensive scientific inquiry, the etiology of recurrent miscarriage remains elusive in roughly half of cases. Among the potential causative agents for fetal well-being threats, viral infections are the most prevalent cause of congenital infections. Evidence suggests that Cytomegalovirus infections may contribute to pregnancy loss in women. Blood type has also been linked to a host of diseases, serving as receptors or co-receptors for pathogens and promoting the uptake of viral particles into cells. Therefore, comprehending the role of these factors in recurrent miscarriage is essential for designing effective prevention and treatment strategies for this condition. Materials and Methods: In the period spanning from September 2022 to January 2023, 64 women who had experienced recurrent miscarriages were selected for blood sample collection. Sera were separated to diagnose CMV-IgG by Chemiluminescence immunoassay. Additionally, the ABO blood group was detected in the patients. Results: Nearly 78.1% of participants were positive for anti CMV-IgG, with the highest percentage of infection found in the age group of 26 to 35 years and individuals with blood group (O+) being more susceptible to infection. Conclusion: Blood group O acts as risk factor for recurrent miscarriages caused by CMV infection.